Praktikalitas Aplikasi Media Pembelajaran Berbasis Augmented Reality pada Mata Pelajaran Perawatan Wajah, Badan (Body Massage) dan Waxing : (Studi Kasus Kelas XI Kecantikan SMKN 7 Padang) - Sobaria, Sobaria; Yuliawati Yunus; Rahmatul Husna Arsyah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determine the practicality of designing and developing Android-based learning media applications for facial, body massage and waxing subjects at SMK N 7 Padang in the 2022/2023 school year. This research uses research and development methods (Research & Development). The research subjects were 78 students of SMK Negeri 7 Padang. This research method uses analysis (ADDIE), with the design and development steps as follows. (1) Analyze, (2) Design, (3) Development, (4) Implementation, and (5) Evaluate. The results of the practicality test assessment as a whole the practicality assessment of the Android-Based Learning Media Application in the subject of Facial, Body Massage and Waxing Class XI Beauty Department at SMK Negeri 7 Padang is 94.44%, so that the level of practicality can be interpreted as very practical to use. In conclusion, based on assessments along with expert input as well as from the results of field trials of the Android-Based Learning Media Application as a learning medium, it has been tested for feasibility, superiority, and used in the learning process in the subject of Face Care, Body (Body Massage) and Waxing for Class XI Beauty Department at SMK Negeri 7 Padang.